Binary combinations of organophosphorus and synthetic pyrethroids are more potent acetylcholinesterase inhibitors than organophosphorus and carbamate mixtures: An in vitro assessment. (15th February 2017) - Arora, Sumitra; Balotra, Sahil; Pandey, Gunjan; Kumar, Anu
Highlights: In - vitro mixture toxicity of five organophosphates and two carbamates pesticides in binary combinations was investigated. Housefly head acetylcholinesterse based bioassays showed differential toxicity under oxidised and un-oxidised conditions. Eight binary combinations exhibited synergistic effects under oxidised conditions Triazophos in binary combination with carbaryl and carbofuran exhibited synergistic effects. Organophosphate pesticides exhibited greater acetylcholinesterase inhibition in combination with pyrethroids. Abstract: Anticholinesterase insecticides such as organophosphorous (OP) and carbamates pesticides (CB); and synthetic pyrethroids (SP) pesticides commonly co-occur in the environment. This raises the possibility of antagonistic, additive, or synergistic neurotoxicity in exposed organisms. Acetylcholinesterase (AChE) inhibition has been demonstrated to be useful as a biomarker for exposure to OP and CBs in many environments. This study investigated the response of housefly ( Musca domestica ) head AChE (HF-AChE) exposed to five OPs; chlorpyrifos (CPF), malathion (MLT), triazophos (TRZ), monocrotophos (MCP) and profenofos (PRF) and two CBs; carbaryl (CRB) and carbofuran (CBF) as individual compounds and as binary mixtures of OPs and CBs under in vitro conditions. In addition, the selected OPs and CBs were evaluated for their toxicity in binary combinations with two SPs; deltamethrin (DLT) and cypermethrin (CYP) at fixed concentrations of 0.1 and 10 μg/L. The toxicological interaction of five OPs with two CBs pesticides was evaluated under oxidised and un-oxidised conditions using a toxic unit (TU) approach and a concentration addition (CA) model. Pyrethroid combinations were assessed only under oxidised conditions. Since OPs and CBs act by a similar mechanism of inhibition of AChE, a dose additive effect was expected, but not conclusively found. TRZ with either CBF or CRB exhibited synergism under oxidised and un-oxidised conditions but the degree of synergism was stronger under un-oxidised conditions. Additivity was exhibited by CBF + MCP, CRB + MCP, CRB + MLT and CBF + MCP under un-oxidised conditions and CRB + MCP and CRB + CPF under oxidised conditions. Pyrethorids in combination with OPs (TRZ, MLT and CPF) were highly synergistic. In the present study, we used pure housefly head AChE without any interference of monooxygenase and/or esterase enzyme activities. Therefore these other enzymes were not producing the observed deviations from concentration-addition in the binary combinations between OPs, CBs and SPs. The mechanisms of OP, CB and SP interactions in pesticide mixtures requires further investigation.